2018
DOI: 10.1371/journal.pone.0193999
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional characterization of the DA2 receptor gene in Chinese mitten crab (Eriocheir sinensis)

Abstract: Dopamine (DA) plays a modulatory role in numerous physiological processes such as light adaptation and food intake, and exerts these functions through DA receptors (DARs). This study presents, for the first time, isolation and characterization of the dopamine receptor 2(DA2 receptor) cDNA from the intestinal tissue of Eriocheir sinensis, an economically important freshwater aquaculture species in China. The DA2 receptor cDNA sequence, which was obtained by rapid amplification of cDNA ends, is 2369bp long, enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The total RNA of the cerebral ganglion and thoracic ganglia was extracted using RNAiso Plus reagent . The mRNA levels of 5-HT2B, 5-HT7, and DA2 receptors were determined using an ABI 7500 real-time PCR system (Life Technology, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total RNA of the cerebral ganglion and thoracic ganglia was extracted using RNAiso Plus reagent . The mRNA levels of 5-HT2B, 5-HT7, and DA2 receptors were determined using an ABI 7500 real-time PCR system (Life Technology, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The total RNA of the cerebral ganglion and thoracic ganglia was extracted using RNAiso Plus reagent. 33 The mRNA levels of 5-HT2B, 5-HT7, and DA2 receptors were determined using an ABI 7500 real-time PCR system (Life Technology, USA). The 5-HT and DA receptors were detected with gene-specific primers (Table 3), and 18S rRNA was used as the reference gene.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used 18S ribosome RNA (18S) as a reference gene. The DEGs expression levels were calculated using the 2 -ΔΔCt method [23].…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, we found that the eyestalks of E . sinensis express the DA2 receptor which participates in light adaptation during the dark hours [23]. However, there still lack information about the influence of photoperiods on the gene expression of eyestalk ganglion in E .…”
Section: Introductionmentioning
confidence: 99%